Adsorption of symmetric random copolymer onto symmetric random surface: the annealed case - Polotsky, A.A. (Condensed Matter Physics, 2015)
Adsorption of a symmetric (AB) random copolymer (RC) onto a symmetric (ab) random heterogeneous surface (RS) is studied in the annealed approximation by using a two-dimensional partially directed walk model of the polymer. We show that in the symmetric case, the expected a posteriori compositions of the RC and the RS have correct values (corresponding to their a priori probabilities) and do not change with the temperature, whereas second moments of monomers and sites distributions in the RC and RS change. This indicates that monomers and sites do not interconvert but only rearrange in order to provide better matching between them and, as a result, a stronger adsorption of the RC on the RS. However, any violation of the system symmetry shifts equilibrium towards the major component and/or more favorable contacts and lead to interconversion of monomers and sites. Адсорбцiя симетричного (AB ) випадкового кополiмера (ВК) на симетричну (ab ) випадкову неоднорiдну поверхню (ВП) вивчається у наближеннi вiдпалу iз використаннями для полiмера двовимiрної моделi частково напрямлених блукань. Показано, що у симетричному випадку очiкуванi a posteriori концентрацiї ВК i ВП мають правильнi значення (якi вiдповiдають їх a priori ймовiрностям) i не змiнюються, в залежностi вiд температури, в той час, як другi моменти розподiлiв мономерiв i вузлiв в ВК i ВП змiнюються. Це показує, що мономери i вузли взаємно не перетворюються, а лише перегруповуються, щоб забезпечити краще допасовування мiж ними i, як результат, сильнiшу адсорбцiю ВК на ВП. Проте будь-яке порушення симетрiї системи зсуває рiвновагу у напрямку основної компоненти i/або до бiльш сприятливих контактiв та приводить до взаємоперетворення мономерiв i вузлiв.